A Comprehensive Guide to Nanoparticles in Medicine - Acharya, Rituparna (Bentham Science Publishers, 2021)
This handbook explains the application of nanoparticles in medical diagnosis and treatment. It is a ready reference on the subject, starting with the introduction to nanoparticles and progressing to synthetic procedures for nanotherapeutics, human disease diagnosis and nanocarrier-based drug delivery. The book also covers information about specific nanoparticle conjugates, in which nanoparticles are combined with drugs or nucleic acid strands (DNA, siRNAs, shRNAs, miRNAs) as well as topics of relevant to this field such as immunotherapy and vaccination development strategies. Each chapter also provides references for further reading. A Comprehensive Guide to Nanoparticles in Medicine is an ideal resource for scholars in medicine, pharmacology and technology who require an understanding to some basic facets of nanoparticles.